Inter Programming Models for the Target Visitation Problem (Informatica, 2015)
The target visitation problem (TVP) is concerned with finding a route to visit a set of targets startingfrom and returning to some base. In addition to the distance traveled a tour is evaluated by taking alsopreferences into account which address the sequence in which the targets are visited. The problem thusis a combination of two well-known combinatorial optimization problems: the traveling salesman and thelinear ordering problem. In this paper we point out some polyhedral properties and develop a branch-andcutalgorithm for solving the TVP to optimality. Some computational results are presented.